Transformasi Pembelajaran Menulis Melalui Media Visual Dalam Konteks Pembelajaran Abad 21 - Anita Candra Dewi (FKIP UNSULTRA, 2025)
Writing learning in the digital era has undergone significant transformations along with the development of technology and visual media. This research is a literature review that aims to explore how visual media contributes to improving students' writing skills, especially at the elementary level. Conventional writing learning often limits students' ability to express ideas, especially for those who have a tendency to learn visually. Visual media such as images, infographics, animated videos, digital comics, and storyboards have been proven to stimulate imagination, facilitate understanding of writing structure, and increase students' writing motivation. This study collected and analyzed various scientific sources from national and international journals between 2019 and 2024. The results of the study indicate that visual media plays a role in improving the quality of students' writing in terms of content, structure, and creativity. Four important aspects that are highlighted are: (1) increasing ideas and imagination, (2) understanding of text structure, (3) motivation and interest in writing, and (4) collaboration and active participation of students in the writing process. This study recommends the systematic integration of visual media into the Indonesian language curriculum to make writing learning more contextual, creative, and appropriate to the demands of the 21st century.